Mammographic tumour appearance and triple-negative breast cancer associated with long-term prognosis of breast cancer death: A Swedish Cohort Study. Issue 2 (April 2015) - Tsau, Huei-Shian; Yen, Amy Ming-Fang; Fann, Jean Ching-Yuan; Wu, Wendy Yi-Ying; Yu, Cheng-Ping; Chen, Sam Li-Sheng; Chiu, Sherry Yueh-Hsia; Tabár, László; Kuo, Wen-Hung; Chen, Hsiu-Hsi; Chang, King-Jen
Highlights A Bayesian approach was conducted to capture the evolution of tumour attributes. Casting and architecture distortion contribute 10- and 4-fold risk for TNBC and NTN. The effect of triple-negative was noted only in casting and architecture distortion.